2021
DOI: 10.3390/ijerph18168293
|View full text |Cite
|
Sign up to set email alerts
|

Comparatively Analyzing the Impact of Government Subsidy and Carbon Tax Policy on Authorized Remanufacturing

Abstract: Authorized remanufacturing is an important means to achieve green manufacturing and carbon neutrality. In this study, a game theory model between a manufacturer and a remanufacturer was constructed to analyze the impact of government subsidies and carbon tax policies on authorized remanufacturing. Based on the game theory model, the effects of two government policies on the optimal solution, namely, the unit cost of remanufacturing product authorization and the waste product recovery rate, were compared and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 53 publications
(77 reference statements)
0
10
0
Order By: Relevance
“…Since carbon trade costs are directly amortized over new products, to maintain the sales volume of new and remanufactured products, OEMs need to adjust outsourcing fees based on the increasing level of carbon trade costs, and then weigh the benefits of the two products. It can be seen that the mechanism is very similar to the impact of the carbon tax on unit retail prices [54].…”
Section: Results Analysismentioning
confidence: 81%
See 2 more Smart Citations
“…Since carbon trade costs are directly amortized over new products, to maintain the sales volume of new and remanufactured products, OEMs need to adjust outsourcing fees based on the increasing level of carbon trade costs, and then weigh the benefits of the two products. It can be seen that the mechanism is very similar to the impact of the carbon tax on unit retail prices [54].…”
Section: Results Analysismentioning
confidence: 81%
“…Similar to [54], the unit retail price of new products is theoretically not affected by consumer preference. As the public favors remanufactured products, however, the OEMs will see decreased sales of new products and potential profit loss under the carbon trade policy.…”
Section: The Impact Of Q and δ On The Unit Retail Prices Of Two Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tan et al [38] studied the impact of the manufacturer's two remanufacturing models on the supply chain, and the results showed that, for a market with obvious green consumerism, self-remanufacturing is more beneficial. Li et al [39] constructed a game theory model between a manufacturer and a remanufacturer under government subsidies and carbon tax policies. Luo et al [40] developed four game theory models to evaluate the impact of the carbon tax policy on manufacturing and remanufacturing decisions in a closed-loop supply chain.…”
Section: Remanufatured Supply Chain Managementmentioning
confidence: 99%
“…Taking the Bohai Bay region of China as an example, the impact of the carbon tax rate and tax cycle share on the economy and carbon emissions has been discussed by Sun et al [10]. Based on the game theory model, the influence of the government subsidy policy and carbon tax policy on the optimal solution of the remanufacturing model was compared by Li et al [11].…”
Section: Introductionmentioning
confidence: 99%